Longitudinal changes in medical complications in adults with pediatric-onset spinal cord injury - Hwang, Miriam (Maney Publishing, 2014)
OBJECTIVES: To determine longitudinal changes in the occurrence of medical complications in adults with pediatric-onset spinal cord injury (SCI). DESIGN: Longitudinal study of long-term outcomes. SETTING: Community. PARTICIPANTS: Individuals who had sustained an SCI before age 19, were 23 years of age or older at initial interview, and followed annually between 1996 and 2011. They were classified into four American Spinal Injury Association (ASIA) Impairment Scale (AIS) severity groups: C1–4 AIS ABC, C5–8 AIS ABC, T1–S5 AIS ABC, AIS D. OUTCOME MEASURES: Generalized estimating equation (GEE) models were formulated to obtain the odds ratio (OR) of having a medical complication over time. RESULTS: A total of 1793 interviews were conducted among 226 men and 125 women (86% Caucasian; age at baseline, 26.7 ± 3.6 years; time since injury at baseline, 12.9 ± 5.2 years). Odds of complication occurrence over time varied among severity groups, with increased ORs of severe urinary tract infection (1.05, confidence interval (CI) 1.02–1.09), autonomic dysreflexia (AD) (1.09, CI 1.05–1.14), spasticity (1.06, CI 1.01–1.11), pneumonia/respiratory failure (1.09, CI 1.03–1.16), and hypertension/cardiac disease (1.07, CI 1.01–1.15) in the C1-4 ABC group; AD (1.08, CI 1.04–1.13) and pneumonia/respiratory failure (1.09, CI 1.02–1.16) in the C5–8 ABC group; and hypertension/cardiac disease (1.08, CI 1.02–1.14) in the T1–S5 ABC group. Upper extremity joint pain had increased odds of occurrence in all injury severity groups. CONCLUSION: The significantly increased odds of having medical complications over time warrants awareness of risk factors and implementation of preventive measures to avoid adverse consequences of complications and to maintain independence in individuals with pediatric-onset SCI.